The Influence of Digital Leadership on Innovative Work Behavior with Digital Self-Efficacy as a Mediating Variable and Organizational Learning Culture as a Moderating Variable Among Civil Servants in Regency X - Lina Apriliani; Ahmad Hanfan (Indonesian Interdisciplinary Journal of Sharia Economics (IIJSE), 2026)
This study examines the effect of digital leadership on innovative work behavior with digital self-efficacy as a mediating variable and organizational learning culture as a moderating variable among civil servants. Using a quantitative explanatory approach with a survey design, data were collected from 200 civil servants in Regional Government Organizations in Central Java Province and analyzed using Partial Least Squares Structural Equation Modeling (PLS-SEM) with SmartPLS 4. The findings show that digital leadership has a positive and significant effect on innovative work behavior (β=0.312; p<0.01) both directly and through the mediation of digital self-efficacy (β indirect=0.154; p<0.01). Digital leadership is also a strong predictor of digital self-efficacy (β=0.483; p<0.01). However, organizational learning culture does not moderate the relationship between digital self-efficacy and innovative work behavior (β=0.050; p=0.448). These findings confirm that effective digital leadership, supported by employees’ digital self-confidence, is a key determinant of innovative work behavior in the era of digital transformation.